Analisis Strategi Pengembangan Usaha Ekonomi Kreatif (Studi Kasus Pada Sentra Kerajinan Tangan Anjoroku di Kabupaten Kepulauan Selayar) - Mega Krisdayani; Muh. Ihsan Said Ahmad; Marhawati Marhawati; Mustari Mustari; Syamsu Rijal (Indonesian Journal of Social and Educational Studies, 2020)
This research aims to determine the business development strategy of Anjoroku Handicraft Center in Selayar Islands Regency. This research is categorized as qualitative research. The data was collected by means of observation, interview and documentation techniques. The analysis technique used is the SWOT analysis. The results show that the development strategy that can be applied in the Anjoroku Handicraft Center business in Selayar Islands Regency is in quadrant I, which is a strategy to support aggressive growth policies. This aggressive strategy is more focused on the SO (Strength-Opportunities) strategy, namely by using strength to take advantage of existing opportunities. The SO strategy is: maximizing the production of souvenirs with various variants, developing businesses using capital assistance from the government, maintaining product uniqueness in order to dominate the market, maximizing promotions to be better known to consumers, and improving service quality in order to always create a good impression in the eyes of consumers.